Static Shear Strength of a Non-Prismatic Beam with Transverse Openings - Al-Hilali, A. M.; Izzet, A. F.; Oukaili, N. (Engineering, Technology & Applied Science Research, 2022)
In this study, a predicated formula is been proposed to find the shear strength of non-prismatic beams with or without openings. It depends on the contributions of concrete shear strength considering the beam depth variation and existing openings, shear steel reinforcements and defines the critical shear section, the effect of diagonal shear reinforcement, the effect of inclined tensile steel reinforcement, and the compression chord influence. The verification of the proposed formula has been conducted on the experimental test results of 26 non-prismatic beams with or without openings at the same loading conditions. The results reflect that the predicted formula finds the shear capacity of non-prismatic beams with openings, it is conservative and can be used for designing without the strength reduction factor.